Dermatoglyphics Pattern on Breast Cancer Patients in Dharmais Cancer Hospital - Faras Qodriyyah Sani; Mirfat Mirfat; Iskandar Iskandar (Global Medical & Health Communication (GMHC), 2020)
Dermatoglyphics is a study of the epidermal ridge in fingers, palms, soles, toes, and formed under genetic control at the beginning of the development of the fetus around 6–7 weeks and continues until 20–21 weeks. The development of the breast begins in a 6-week-old fetus in the epidermis and at the bottom of the mesenchyme. The development of the finger ridges and breast occurs at six weeks of gestation, and the abnormal genomes can be detected at this period and observed through dermatoglyphics. The purpose of this study was to determine the dermatoglyphic patterns of breast cancer patients in Dharmais Cancer Hospital from 12 December 2018 to 1 January 2019. The study was a descriptive study with a purposive sampling method for the determination of the sample. The quantitative data collected using questionnaires while the prints of dermatoglyphic patterns were from the fingertips of the respondent. From 100 respondents, the left-hand fingers and right-hand fingers dominated by radial loop pattern with the most significant percentage on the middle finger 62% and 77%, respectively. While the ring finger dominated by the plain whorl pattern 43%. In conclusion, the dermatoglyphics pattern on breast cancer patients in Dharmais Cancer Hospital dominated by a radial loop pattern. POLA DERMATOGLIFI TANGAN PASIEN KANKER PAYUDARA DI RUMAH SAKIT KANKER DHARMAISDermatoglifi merupakan ilmu yang mempelajari tentang pola sulur pada jari, telapak tangan, telapak kaki, dan jari kaki yang terbentuk di bawah kontrol genetik pada awal perkembangan usia janin sekitar 6–7 minggu serta terus berkembang sampai usia 20–21 minggu. Perkembangan payudara dimulai pada janin berusia 6 minggu dalam bentuk gumpalan padat yang berada di epidermis dan di bagian bawah mesenkim. Perkembangan sulur dermal dan payudara terjadi pada usia kehamilan enam minggu dan genom tidak abnormal dapat dideteksi pada periode ini dan dapat teramati melalui dermatoglifi. Tujuan penelitian ini mengetahui pola dermatoglifi pada pasien kanker payudara di Rumah Sakit Kanker Dharmais dari tanggal 12 Desember 2018 hingga 1 Januari 2019. Penelitian ini merupakan studi deskriptif dengan metode purposive sampling untuk penentuan sampel. Data kuantitatif diperoleh dengan menggunakan kuesioner, sedangkan cetakan pola dermatoglifi berasal dari ujung jari tangan responden. Dari 100 responden, jari tangan kiri dan jari tangan kanan didominasi oleh pola radial loop dengan persentase terbesar pada jari tengah sebesar 62% dan 77% masing-masing. Sementara jari manis didominasi oleh pola plain whorl sebesar 43%. Simpulan, pola dermatoglifi pada pasien kanker payudara di Rumah Sakit Kanker Dharmais didominasi oleh pola radial loop.